2020
DOI: 10.1097/mpg.0000000000002997
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Fibrosis in Eosinophilic Gastrointestinal Diseases

Abstract: Objectives: Eosinophilic esophagitis (EoE), the most common eosinophilic gastrointestinal disease (EGID), is associated with lamina propria (LP) fibrosis. The relationship of EoE to other EGIDs is still unclear. We frequently observe cases of concurrent esophageal eosinophilia and extra-esophageal mucosal eosinophilia. The purpose of this study was to compare clinical, endoscopic, and histologic features, as well as the prevalence of esophageal LP fibrosis in children with EGID and concurrent esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Future studies are warranted to further test the reproducibility and generalizability of the web‐based predictive models in different populations to make it more robust and reliable, as well as to update the existing web‐based predictive models to provide predictive probability for severity of LPF by sub‐scores (0–3) per EoEHSS. It is conceivable that we might be able to create models to prospectively predict LPF in different EoE phenotypes (17) and consistent evaluation of LPF (18) in EoE patients with high degree of confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are warranted to further test the reproducibility and generalizability of the web‐based predictive models in different populations to make it more robust and reliable, as well as to update the existing web‐based predictive models to provide predictive probability for severity of LPF by sub‐scores (0–3) per EoEHSS. It is conceivable that we might be able to create models to prospectively predict LPF in different EoE phenotypes (17) and consistent evaluation of LPF (18) in EoE patients with high degree of confidence.…”
Section: Discussionmentioning
confidence: 99%
“…6 A subsequent study at our institution confirmed that LP fibrosis not only occurs in EoE, but also in patients with eosinophilic gastrointestinal diseases (EGIDs) with significant esophageal eosinophilia. 7…”
Section: Introductionmentioning
confidence: 99%
“…6 A subsequent study at our institution confirmed that LP fibrosis not only occurs in EoE, but also in patients with eosinophilic gastrointestinal diseases (EGIDs) with significant esophageal eosinophilia. 7 Currently, there is no standard histologic definition of lamina propria fibrosis or its adequacy. Hence, many pathologists do not routinely include such features in their reports.…”
Section: Introductionmentioning
confidence: 99%